A de novo 1p34.2 microdeletion identifies the synaptic vesicle gene RIMS3 as a novel candidate for autism. Issue 2 (21st June 2009) - Kumar, Ravinesh A; Sudi, Jyotsna; Babatz, Timothy D; Brune, Camille W; Oswald, Donald; Yen, Mayon; Nowak, Norma J; Cook, Edwin H; Christian, Susan L; Dobyns, William B
Abstract : Background: A child with autism and mild microcephaly was found to have a de novo 3.3 Mb microdeletion on chromosome 1p34.2p34.3. The hypothesis is tested that this microdeletion contains one or more genes that underlie the autism phenotype in this child and in other children with autism spectrum disorders. Methods: To search for submicroscopic chromosomal rearrangements in the child, array comparative genomic hybridisation (aCGH) was performed using a 19 K whole genome human bacterial artificial chromosome (BAC) array and the Illumina 610-Quad BeadChip microarray. Ingenuity pathway analysis (IPA) was used to construct functional biological networks to identify candidate autism genes. To identify putative functional variants in candidate genes, mutation screening was performed using polymerase chain reaction (PCR) based Sanger sequencing in 512 unrelated autism patients and 462 control subjects. Results: A de novo 3.3 Mb deletion containing ∼43 genes in chromosome 1p34.2p34.3 was identified and subsequently confirmed using fluorescence in situ hybridization (FISH). Literature review and bioinformatics analyses identified Regulating Synaptic Membrane Exocytosis 3 ( RIMS3 ) as the most promising autism candidate gene. Mutation screening of this gene in autism patients identified five inherited coding variants, including one (p.E177A) that segregated with the autism phenotype in a sibship, was predicted to be deleterious, and was absent in 1161 controls. Conclusions: This case report and mutation screening data suggest that RIMS3 is an autism causative or contributory gene. Functional studies of RIMS3 variants such as p.E177A should provide additional insight into the role of synaptic proteins in the pathophysiology of autism.